Pengaruh Corporate Governance dalam Memprediksi Biaya Ekuitas dengan Pendekatan Model Ohlson - Rivandi, Muhammad; Marlina, Marlina (El-Barka Journal of Islamic Economics and Business, 2019)
Abstract: Cost of equity a concept of cost in determining the real cost that must be borne by the company to obtain funds from a source or use of capital from each source of funds, then determine the average cost of capital of all funds used by the company. The method used in the measurement of equity costs is the Ohlson model. Research objectives to prove empirically the Effect of Corporate Governance in Predicting Equity Costs with the Ohlson Model Approach. Research population of manufacturing companies on the Indonesia Stock Exchange. The sample used using porposive sampling techniques amounted to 30 companies. The analysis method used uses a panel regression model. Based on the test results, it is empirically proven that (1) Family Ownership does not affect the cost of Equity, (2) Institutional Ownership negatively affects the cost of equity, (3) The Independent Board of Commissioners does not affect the cost of equity. Ø§Ù„Ù…Ù„Ø®Øµ: ØªÙƒÙ„ÙØ© Ø§Ù„Ø£Ø³Ù‡Ù… Ù‡ÙŠ Ù…ÙÙ‡ÙˆÙ… Ø§Ù„ØªÙƒÙ„ÙØ© ÙÙŠ ØªØØ¯ÙŠØ¯ Ù…Ù‚Ø¯Ø§Ø± Ø§Ù„ØªÙƒØ§Ù„ÙŠÙ Ø§Ù„ØÙ‚ÙŠÙ‚ÙŠØ© Ø§Ù„ØªÙŠ ÙŠØ¬Ø¨ Ø£Ù† ØªØªØÙ…Ù„Ù‡Ø§ Ø§Ù„Ø´Ø±ÙƒØ© Ù„Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø£Ù…ÙˆØ§Ù„ Ù…Ù† Ù…ØµØ¯Ø± Ø£Ùˆ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø±Ø£Ø³ Ø§Ù„Ù…Ø§Ù„ Ù…Ù† ÙƒÙ„ Ù…ØµØ¯Ø± Ù„Ù„Ø£Ù…ÙˆØ§Ù„ØŒ Ø«Ù… ØªØØ¯ÙŠØ¯ Ù…ØªÙˆØ³Ø· ØªÙƒÙ„ÙØ© Ø±Ø£Ø³ Ø§Ù„Ù…Ø§Ù„ (Ù…ØªÙˆØ³Ø· ØªÙƒÙ„ÙØ© Ø±Ø£Ø³ Ø§Ù„Ù…Ø§Ù„) Ù„Ø¬Ù…ÙŠØ¹ Ø§Ù„ØµÙ†Ø§Ø¯ÙŠÙ‚ Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„Ø´Ø±ÙƒØ©. Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‚ÙŠØ§Ø³ ØªÙƒØ§Ù„ÙŠÙ Ø§Ù„Ø£Ø³Ù‡Ù… Ù‡ÙŠ Ù†Ù…ÙˆØ°Ø¬ Ø£ÙˆÙ„Ø³ÙˆÙ†. Ø§Ù„Ù‡Ø¯Ù Ù…Ù† Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡Ùˆ Ø¥Ø«Ø¨Ø§Øª Ù…Ù„ÙƒÙŠØ© Ø§Ù„Ø£Ø³Ø±Ø© Ø¨Ø´ÙƒÙ„ ØªØ¬Ø±ÙŠØ¨ÙŠØŒ ÙˆØ§Ù„Ù…Ù„ÙƒÙŠØ© Ø§Ù„Ù…Ø¤Ø³Ø³ÙŠØ©ØŒ ÙˆÙ…Ø¬Ù„Ø³ Ù…ÙÙˆØ¶ÙŠÙ† Ù…Ø³ØªÙ‚Ù„ÙŠÙ† ØÙˆÙ„ ØªÙƒÙ„ÙØ© Ø§Ù„Ø£Ø³Ù‡Ù…. Ø§Ù„Ø¨ØÙˆØ« Ø§Ù„Ø³ÙƒØ§Ù†ÙŠØ© Ù„Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø´Ø±ÙƒØ§Øª ÙÙŠ Ø¨ÙˆØ±ØµØ© Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§. ÙƒØ§Ù†Øª Ø§Ù„Ø¹ÙŠÙ†Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ØªÙ‚Ù†ÙŠØ© Ø£Ø®Ø° Ø¹ÙŠÙ†Ø§Øª Ù‡Ø§Ø¯ÙØ© Ø¨Ù„Øº Ù…Ø¬Ù…ÙˆØ¹Ù‡Ø§ 30 Ø´Ø±ÙƒØ©. Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠØ© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù‡ÙŠ Ù†Ù…ÙˆØ°Ø¬ Ø§Ù†ØØ¯Ø§Ø± Ø§Ù„Ù„ÙˆØØ©. Ø¨Ù†Ø§Ø¡Ù‹ Ø¹Ù„Ù‰ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø±ØŒ ØªØ«Ø¨Øª Ø¨Ø´ÙƒÙ„ ØªØ¬Ø±ÙŠØ¨ÙŠ Ø£Ù† (1) Ù…Ù„ÙƒÙŠØ© Ø§Ù„Ø£Ø³Ø±Ø© Ù„ÙŠØ³ Ù„Ù‡Ø§ Ø£ÙŠ ØªØ£Ø«ÙŠØ± Ø¹Ù„Ù‰ ØªÙƒÙ„ÙØ© Ø§Ù„Ø£Ø³Ù‡Ù…ØŒ (2) Ø§Ù„Ù…Ù„ÙƒÙŠØ© Ø§Ù„Ù…Ø¤Ø³Ø³ÙŠØ© Ù„Ù‡Ø§ ØªØ£Ø«ÙŠØ± Ø³Ù„Ø¨ÙŠ Ø¹Ù„Ù‰ ØªÙƒÙ„ÙØ© Ø§Ù„Ø£Ø³Ù‡Ù…ØŒ (3) Ù…Ø¬Ù„Ø³ Ø§Ù„Ù…ÙÙˆØ¶ÙŠÙ† Ø§Ù„Ù…Ø³ØªÙ‚Ù„ÙŠÙ† Ù„ÙŠØ³ Ù„Ù‡ Ø£ÙŠ ØªØ£Ø«ÙŠØ± Ø¹Ù„Ù‰ ØªÙƒÙ„ÙØ© ØÙ‚ÙˆÙ‚ Ø§Ù„Ù…Ù„ÙƒÙŠØ©. Abstrak: Biaya ekuitas sebuah Konsep biaya dalam menentukan besarnya biaya secara riil yang harus ditanggung oleh perusahaan untuk memperoleh dana dari suatu sumber atau penggunaan modal dari masing-masing sumber dana, untuk kemudian menentukan biaya modal rata-rata (average cost of capital) dari keseluruhan dana yang dipergunakan perusahaan. Metode yang digunakan didalam pengukuran biaya ekuitas adalah model Ohlson. Tujuan penelitian untuk membuktikan secara empiris Kepemilikan Keluarga, Kepemiikan Institusional, dan Dewan Komisaris Independen Terhadap Biaya Ekuitas. Populasi penelitian perusahaan manufaktur di Bursa Efek Indonesia. Sampel yang digunakan mengunakan teknik porposive sampling berjumlah 30 perusahaan. Metode Analisis yang digunakan menggunakan model regresi panel. Berdasrkan hasil pengujian membuktikan secara empiris bahwa (1) Kepemilikan Keluarga tidak berpengaruh terhadap biaya Ekuitas, (2) Kepemilikan Institusional berpengaruh negatif terhadap biaya ekuitas, (3) Dewan Komisaris Independen tidak berpengaruh terhadap biaya ekuitas.